Pengaruh Kompensasi Finansial dan Non Finansial Terhadap Kinerja Karyawan (Studi pada Pabrik Gula Ngadiredjo, Kediri) - Sianipar, Syahrial Sacharine (Jurnal Ilmiah Mahasiswa FEB, 2014)
The objective of research is to understand the influence of financial and non-financial compensations on employee performance at PG Ngadiredjo Kediri. Type of research is quantitative with explanatory method. The sample is counted for 100 persons and sorted from the population of 1194 persons using proportional random sampling. Analysis method is Multiple Linear Regression Statistic to examine the proposed hypothesis. Result of research has proved three findings, respectively: there is a simultaneous influence of financial and non-financial compensations on employee performance, there is a partial influence of financial and non-financial compensations on employee performance, and financial compensation is the most dominant factor to influence employee performance at Sugar Factory (PG) of Ngadiredjo Kediri. It means that financial and non-financial compensations are significantly improving employee performance at Sugar Factory (PG) of Ngadiredjo Kediri.Â  Keywords: Financial Compensation, Non-Financial Compensation, Sugar Factory (PG) of Ngadiredjo Kediri